Case series of 200 laparoscopic cholecystectomy, their intra-operative finding and post-operative complication - Ahirwar, Sovat Lal (International Surgery Journal, 2019)
Background: In the current era of laparoscopic procedure, laparoscopic cholecystectomy are most commonly performed surgery all over the world. The biliary tract injury by laparoscopic cholecystectomy has been found to be higher than open cholecystectomy. So adequate recognition and awareness of anatomical abnormalities of encounter during laparoscopic cholecystectomy can decrease the morbidity and mortality related to surgery. Methods: It is prospective study including 200 patients based on intra-operative finding and their postoperative complication in Bhopal Memorial Hospital and research centre Bhopal, during period of Jan 2017 to Jan 2019. Results: In 200 cases 154 were Female and 46 were male. Mucocele of gallbladder in 22 cases, pyocele of gall-bladder in 7 cases. Gallbladder wall thickened and fibrosis in 13 cases. Gallbladder with duodenal fistula in 1case, gall bladder with colon and gall bladder with stomach fistula both in 1 case, and gall bladder with stomach fistula in 1 case. In one case there is absent gall bladder but patient havingCBD stone. Cystic artery cant separated from cystic duct and clipped along with cystic duct in 16 cases. In 3 cases there were gall bladder malignancy two were suspected intra-operatively and procedure abandoned other one after post lap cholecystectomy, confirm with biopsy report. Two cases develop post op incisional hernia. In 8 cases lap cholecystectomy converted into open cholecystectomy. Conclusions: This case series of laparoscopic cholecystectomy will help surgeons to be aware of such intra-operative finding and complication, so as to prevent undesirable outcome.